Rituximab - Progress but Still Not a Final Resolution for Pemphigus Patients: Clinical Report From a Single Center Study - Miše, Joško; Jukić, Ines Lakoš; Marinović, Branka (Frontiers in Immunology, 2022)
Pemphigus is a rare autoimmune disease characterized by the production of pathogenic autoantibodies against desmosomal adhesion proteins, desmoglein 1 and 3. The pathophysiological process leads to the development of blisters and erosions on mucosal and/or skin surfaces as the main clinical manifestation of the disease. Rituximab emerged as the first-line therapeutic option for pemphigus due to its ability to induce remission by depleting peripheral B lymphocytes. Our aim was to assess the efficacy of rituximab in the treatment of patients in Croatia. A single-center, retrospective study was conducted on 19 patients treated with rituximab following a rheumatoid arthritis dosing protocol between October 2015 and March 2021, with a mean follow-up of 24.1 months. After the first rituximab cycle, two patients achieved complete remission off therapy (10.5%), and six patients achieved complete remission on minimal therapy (31.6%). Partial remission was observed among ten patients (52.6%). Eight patients (44.4%) relapsed after the first rituximab cycle. The mean relapse time was 21 months. Seven patients received two rituximab cycles, and three patients received three cycles. Overall, 13 out of 19 patients experienced complete remission at some point during the study, while there were no non-responders after the rituximab treatment. No statistically significant associations were observed between age, sex, type of disease involvement and clinical remission, either on or off therapy. A steady decrease in anti-desmoglein 1 and anti-desmoglein 3 levels was measured among all patients following rituximab treatment. One patient experienced a treatment-related adverse event of infectious etiology (cellulitis). One patient died following the first rituximab cycle, with the cause of death likely not to be associated with the treatment. Rituximab is an effective disease-modifying agent in the treatment of pemphigus with the main benefit of reducing corticosteroid exposure and steroid-related side effects among pemphigus patients. However, a feature of rituximab therapy is high relapse rates and the need for repeated treatment cycles to achieve complete remission. Developing an optimal protocol for rituximab treatment and finding suitable markers for predicting relapse will improve the management of pemphigus patients.